2017
DOI: 10.1088/1402-4896/aa8789
|View full text |Cite
|
Sign up to set email alerts
|

Transient induced tungsten melting at the Joint European Torus (JET)

Abstract: Melting is one of the major risks associated with Tungsten Plasma-Facing Components (PFCs) in tokamaks like JET or ITER. These Components are designed such that leading edges and hence excessive plasma heat loads deposited at near normal incidence are avoided. Due to the high stored energies in ITER discharges, shallow surface melting can occur under insufficiently mitigated plasma disruption and so called Edge Localised Modes -Power load transients.A dedicated program was carried out at the Joint European Tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The validity of the geometric projection for the calculation of the parallel power flux at JET, called into question by the first leading edge experiment, was tested experimentally in a second transient melt study using an alternative lamella design with a protruding sloped surface facing the toroidal field allowing direct IR observation of the slope surface [20]. The conclusion of this work, and of the detailed new thermal analysis [19], is that the optical approximation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the geometric projection for the calculation of the parallel power flux at JET, called into question by the first leading edge experiment, was tested experimentally in a second transient melt study using an alternative lamella design with a protruding sloped surface facing the toroidal field allowing direct IR observation of the slope surface [20]. The conclusion of this work, and of the detailed new thermal analysis [19], is that the optical approximation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For an all-W ITER divertor, detailed studies have been performed and are given in refs. [36][37][38][39][40][41]. It was established that melting can and will be a potentially limiting factor and needs to be controlled by shaping and plasma control.…”
Section: From Carbon To Tungstenmentioning
confidence: 99%
“…They are heavily bombarded by energetic particles during plasma shots. Consequently, the temperature of the leading edge could reach the melting point of tungsten, resulting in the movement of molten tungsten in the direction of j × B [17][18][19]. By tilting and shaping of the castellated structure, and by changing its angle with respect to the field line, leading edges can be hidden from the plasma particles.…”
Section: Damage and Melting Test Of Tungsten Blocks By Power Loading mentioning
confidence: 99%
“…It was also found that the molten droplets of W were directed towards the high field side due to j × B force as reported in Refs. [17][18][19].…”
Section: Damage and Melting Test Of Tungsten Blocks By Power Loading mentioning
confidence: 99%